Som e silêncio dos versos : melopeia de Ezra Pound na poesia de Arnaldo Antunes - Prazeres, Rafael Alexandre Gomes dos (2016)
The sound and the silence of a poem allow the first contact between text and reader / listener to anticipate traces of its meaning. This study analyzed the poems "my time", "dog-eat-dog" and "really" from Arnaldo Antunes based on the concept of melopoeia of Ezra Pound, with a view to highlighting the three aspects of reading a poem (image, sound and meaning), valuing the sound as a crucial element for the resolution of the enigmas. The aim of the study was to identify how the macro and micro units of musicality provide similar clues to those presented by the image and found in the meaning of words in favor of the meaning of each of the poems, as has occurred since the Vedic chants, through the classic songs, the various medieval corners and echoing in modern corners. For the development and elucidation of selected paths in the analysis were necessary some poetic contributions from Arnaldo Antunes (1993a and 2009) and his critical remarks on Antunes (2006a). Around the melopoeia, it was necessary resort to the concepts established by Ezra Pound (1968, 1976 and 2006a). Also theoretical support was necessary to identify as oral poetry and performance linked to the voice and the body relate to this music in poems, from the contributions from Paul Zumthor (2010 and 2014). To observe the update of the poetry's chant in contemporary era and also their different ways of intonation, especially in the twentieth century - with the vanguards - and XXI - with technology - the theoretical efforts were essential to Philadelpho Menezes (1992), Augusto de Campos , Pignatari and Haroldo de Campos (1975), Pierre Lévy (2010) and Tatit (2012), among others. This work presents the inscribed musicality in poetry as a key element for an amplified range of its meaning. Thus highlights the need for more focused for a balanced analysis of all the information present in the poem.